2013
DOI: 10.1016/j.gene.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Silencing near tRNA genes is nucleosome-mediated and distinct from boundary element function

Abstract: Transfer RNA (tRNA) genes and other RNA polymerase III transcription units are dispersed in high copy throughout nuclear genomes, and can antagonize RNA polymerase II transcription in their immediate chromosomal locus. Previous work in Saccharomyces cerevisiae found that this local silencing required subnuclear clustering of the tRNA genes near the nucleolus. Here we show that the silencing also requires nucleosome participation, though the nature of the nucleosome interaction appears distinct from other forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Some active tRNA genes have been shown to possess chromatin insulator activity (35,81,82). In addition, extensive work in yeast has demonstrated that active tRNA genes can repress neighboring Pol II genes through tgm silencing (34,83,84). To understand whether AGO2 plays a role in either of these processes, we focused on a region on the p arm of human chromosome 17 that has been previously characterized to have active tRNA genes that can act as insulators (35).…”
Section: Human Argonaute 2 Binds To Actively Transcribed Trna Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some active tRNA genes have been shown to possess chromatin insulator activity (35,81,82). In addition, extensive work in yeast has demonstrated that active tRNA genes can repress neighboring Pol II genes through tgm silencing (34,83,84). To understand whether AGO2 plays a role in either of these processes, we focused on a region on the p arm of human chromosome 17 that has been previously characterized to have active tRNA genes that can act as insulators (35).…”
Section: Human Argonaute 2 Binds To Actively Transcribed Trna Genesmentioning
confidence: 99%
“…The increase in gene expression (FPKM) among genes that flank AGO2-bound tRNA genes upon AGO2 knockdown suggested a cis effect exerted by the actively transcribed tRNA gene upon nearby Pol II genes, similar to tgm silencing in yeast (34,83,84). To address this possibility, we quantified the fold change in each upstream and downstream Pol II gene as a function of its distance from the nearest tRNA gene (Fig.…”
Section: Human Argonaute 2 Binds To Actively Transcribed Trna Genesmentioning
confidence: 99%
“…The involvement of nucleosome surfaces and several chromatin modifying and remodeling enzymes in tgm silencing has been documented, though how the tRNA gene communicates physically with the chromatin is not yet understood (Good et al, 2013). Mutations affecting nucleosome covalent modification and remodeling include those in the RSC nucleosome remodeling complex subunits, Rpd3 deacetylase subunits, Hos1 deacetylase, and the Glc7 phosphatase (Good et al, 2013).…”
Section: The Nuclear Function Of Mod5 Is Distinct From Its Trna-isopementioning
confidence: 99%
“…The involvement of nucleosome surfaces and several chromatin modifying and remodeling enzymes in tgm silencing has been documented, though how the tRNA gene communicates physically with the chromatin is not yet understood (Good et al, 2013). Mutations affecting nucleosome covalent modification and remodeling include those in the RSC nucleosome remodeling complex subunits, Rpd3 deacetylase subunits, Hos1 deacetylase, and the Glc7 phosphatase (Good et al, 2013). Taken together with the association of Mod5 with pre-tRNAs and the transcription complexes, we propose that the Mod5-pre-tRNA complex might help recruit one or more of the chromatin-modifying enzymes that exert a repressive effect on nearby promoters through nucleosome rearrangement.…”
Section: The Nuclear Function Of Mod5 Is Distinct From Its Trna-isopementioning
confidence: 99%
“…Ty3 could use identical genes at widely differing frequencies because of different chromatin contexts. RNAP III genes undergo specific types of epigenetic modifications and bind chromatin remodelers and condensins (179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190). In addition to possible differences in chromatin context, tDNAs also act as replication fork barriers (191), and subpopulations localize to the nucleolus (31,192) and nuclear pores (30).…”
Section: Genomewide Identification Of Ty3 Targets and Rnap III Factormentioning
confidence: 99%